Uji Aktivitas Antioksidan dan Penentuan Nilai Sun Protection Factor (SPF) Sediaan Lip Balm Ekstrak Kayu Secang (Caesalpinia Sappan L.) - Nugrahaeni Ayuningtyas; Niken Luthfiyanti; Bangkit Riska Permata (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Sappan wood (Caesalpinia sappan L.) is known to contain various bioactive compounds such as saponins, tannins, flavonoids, phenols, brazilin, and gallic acid. These compounds play an important role as antioxidants that can ward off free radicals and absorb UVA and UVB radiation that are harmful to the skin. Ultraviolet radiation is known to accelerate premature aging and cause tissue damage, so a topical formulation is needed that can provide protection while maintaining skin health. This study aims to determine the antioxidant activity and sunscreen ability of sappan wood extract in the form of lip balm with varying extract concentrations. Antioxidant activity was evaluated using the DPPH (1,1-Diphenyl-2-Picrylhydrazyl) method, while the Sun Protection Factor (SPF) value was determined by the Mansyur method using UV-Vis spectrophotometry. Sappan wood extract was formulated into four lip balm preparations, namely F0 (control without extract), F1 (5%), F2 (10%), and F3 (15%). Physical tests including homogeneity, pH, spreadability, adhesiveness, and organoleptic were conducted to ensure the quality of the preparation. The results showed that sappanwood extract had an IC50 value of 23.62 ppm which was categorized as very strong antioxidant activity. In the lip balm formulation, the IC50 values ​​obtained were F0 = 246.76 ppm (very weak), F1 = 92.68 ppm (strong), F2 = 78.03 ppm (strong), and F3 = 63.58 ppm (strong). The SPF test showed a protection value of F0 = 2.11 (minimum), F1 = 13.64 (maximum), F2 = 14.25 (maximum), and F3 = 18.28 (ultra). Thus, lip balm made from sappanwood extract has the potential as a cosmetic preparation that not only meets physical criteria, but also provides high antioxidant activity and effective sunscreen protection.